PTEN gene mutation in endometrial carcinoma correlation with age and grade - H. Kareem, Emad; S. AL-Shemmary, Alaa (Al-Qadisiyah Journal of Pure Science, 2018)
The present study has been conducted to evaluate the effect of PTEN gene mutation in endometroid endometrial carcinoma through estimate the correlation PTEN expression with some clinico pathological feature (age and grading) of this cancer. Collect Forty three samples of endometroid endometrial carcinoma and twenty non-malignant samples .all samples were formalin fixed and paraffin embedded tissue collected from january 2008 to 2014 from Iraqi histopathological laboratories , after extract the total RNA the cDNA synthesis and amplification by qRT_PCR then calculate the result via relative (Livak) method. The statistical analyses reveal that no correlation between pten expression and advancing age.on other hand the study establish a positive correlation between PTEN expression and mean grad of tumor.